Identity of Genes Coding for Soluble and Structural Dihydrofolate Reductases in Bacteriophage T4 - Mathews, Christopher K. (1971)
By recombination between bacteriophage T4 wh2, a dihydrofolate reductaseless mutant, and T6, I have prepared T4 wh(T6), a T4 strain which codes for the T6-specific soluble dihydrofolate reductase. This strain has the heat sensitivity of T6, not T4, which provides direct evidence that the wh gene codes for both the soluble dihydrofolate reductase and the structural dihydrofolate reductase which is a constituent of T-even phage tail plates.